A general charge compensation strategy for calibrating the voltage of a triboelectric nanogenerator measured by a capacitive circuit. (August 2021) - Zhang, Wenhe; Gu, Guangqin; Shang, Wanyu; Luo, Hongchun; Wang, Tingyu; Zhang, Bao; Cui, Peng; Guo, Junmeng; Yang, Feng; Cheng, Gang; Du, Zuliang
Abstract: The voltage is a key parameter of a triboelectric nanogenerator (TENG). However, when the voltage is measured by the voltmeters with a capacitive measurement circuit, there is a charge transfer between the TENG and the inner capacitor, making the measured voltage lower than its actual value. In this paper, a general charge compensation strategy is proposed for calibrating the measured voltage of a TENG based on the analysis of the capacitive measurement circuit. Two methods, the fixed capacitance derivation (FCD) and the variable capacitance fitting (VCF), are developed to calibrate the open-circuit voltage ( V oc ) of TENGs, and the calibration formulas of V oc are given, respectively. Firstly, a sliding freestanding triboelectric-layer mode TENG is taken as an example and the two methods are used to calibrate actual V oc . The results are consistent with that measured by the ammeter with non-capacitive measurement circuit, verifying the validity of the charge compensation strategy. For the other three basic working modes TENGs, the measured V oc are calibrated by the FCD method, which illustrate the universality of the charge compensation strategy. Finally, the relationship between the output voltage of a TENG and the load impedance is calibrated through the equivalent impedance including the inner capacitance of the voltmeter. The proposed charge compensation strategy for calibrating the voltage of a TENG measured by a capacitive circuit is of great theoretical and application significance for the establishment of a comprehensive evaluation system for TENG's output performance. Graphical Abstract: This paper proposed a general charge compensation strategy for calibrating the measured voltage of a TENG. The fixed capacitance derivation and the variable capacitance fitting are developed to calibrate the open-circuit voltage of TENGs. The output voltage of a TENG is calibrated through the equivalent impedance including the inner capacitance of the voltmeter. ga1 Highlights: Charge transfer between TENG and the inner capacitor of voltmeters makes the measured voltage lower than its actual value. A general charge compensation strategy is proposed for calibrating the measured voltage of a TENG. The FCD method and VCF method are developed to calibrate the open-circuit voltage of TENGs. The output voltage of a TENG is calibrated through the equivalent impedance including the inner capacitance of voltmeter.